Bioinspired Interfacial Materials: A Multi‐Bioinspired Dual‐Gradient Electrode for Microbubble Manipulation toward Controllable Water Splitting (Adv. Mater. 17/2020). Issue 17 (27th April 2020) - Long, Zhiyun; Zhao, Yuyan; Zhang, Chunhui; Zhang, Yuheng; Yu, Cunming; Wu, Yuchen; Ma, Jun; Cao, Moyuan; Jiang, Lei
Abstract : Bioinspired interfacial materials offer great opportunity to manipulate the fluid behavior in versatile systems. In article number 1908099, Jun Ma, Moyuan Cao, and co‐workers present a multi‐bioinspired electrode for regulating the gas generation in water splitting. The highly controllable gas transport facilitates efficient in situ H2 /O2 separation without applying the membrane apparatus, showing a new paradigm of a water‐splitting interface.